Identification of tyrosine sulfation in the variable region of a bispecific antibody and its effect on stability and biological activity - Christopher B. Lietz; Ekaterina Deyanova; Younhee Cho; Jon Cordia; Sarah Franc; Sally Kabro; Steven Wang; David Mikolon; Douglas D. Banks (mAbs)
Despite tyrosine sulfation being a relatively common post-translational modification (PTM) on the secreted proteins of higher eukaryotic organisms, there have been surprisingly few reports of this modification occurring in recombinant monoclonal antibodies (mAbs) expressed by mammalian cell lines and even less information regarding its potential impact on mAb efficacy and stability. This discrepancy is likely due to the extreme lability of this modification using many of the mass spectrometry methods typically used within the biopharmaceutical industry for PTM identification, as well as the possible misidentification as phosphorylation. Here, we identified sulfation on a single tyrosine residue located within the identical variable region sequence of a 2 + 1 bispecific mAbs heavy and heavy-heavy chains using a multi-enzymatic approach in combination with mass spectrometry analysis and examined its impact on binding, efficacy, and physical stability. Unlike previous reports, we found that tyrosine sulfation modestly decreased the mAb cell binding and T cell-mediated killing, primarily by increasing the rate of antigen disassociation as determined from surface plasmon resonance-binding experiments. We also found that, while this acidic modification had no significant impact on the mAb thermal stability, sulfation did modestly increase its rate of aggregation, presumably by lowering the mAb’s colloidal stability as indicated by polyethylene glycol induced liquid–liquid phase separation experiments.